PS-030 Off-label use of anticancer drugs: Which benefits and how much?. (14th February 2016) - Leromain, AS; Dimartino, C; Schmitt, A; Coudert, B; Duban, M
Abstract : Background: Off-label prescribing is frequent in oncology, and its appropriate use represents a major challenge for healthcare providers. In 2010, our reference centre in cancer research organised weekly multidisciplinary meetings to gather clinicians, pharmacists and nurses in order to work on off-label therapies. The purpose was to determine that the prescribing ensured an optimal risk-benefit ratio for individual patients. Purpose: This retrospective study was performed to describe off-label prescriptions in this hospital: patients, cancer sites, stages and/or lines of therapy, medical benefits in terms of survival and economic impact of off-label chemotherapies. Material and methods: Every patient who had an off-label prescription of an anticancer drug in 2011 or 2012 was included. Median overall survival was estimated for the more frequent cancer sites involved, and the economic impact was estimated in terms of medicines spending only. Results: In 2011 and 2012, 304 patients had off-label anticancer treatment; each year, 2000 patients are followed in this hospital. One-third of prescribing occurred in advanced stages of diseases without existing standards of care: glioblastoma (26.3%) and sarcoma (6%). With bevacizumab and trabectedin uses in those indications, median overall survival were, respectively, estimated as 6 and 11 months. 14% of patients had FOLFIRINOX chemotherapy (irinotecan, 5-fluorouracil, leucovorin, oxaliplatin) to treat metastatic pancreatic cancers; median overall survival was estimated at 10 months. Almost 46% of off-label prescriptions included novel chemotherapy at a total cost of €2.8 million. Conclusion: As others studies have showed, most off-label prescriptions occurred in palliative situations to treat advanced stages and rare tumours, but also in new indications, supported by scientific evidences, which have not yet passed through the labelling process. 1, 2 Median overall survival obtained in our study was similar to clinical trial results that led to their off-label uses in those three diseases. This new type of work will serve a global strategy to share off-label prescribing experiences between hospitals from the same territory in order to harmonise and improve medical practices and to help guarantee equality of care. References and/or Acknowledgements: Conti RM. J Clin Oncol 2013 Levêque D. Lancet Oncol 2008 No conflict of interest.